Cambios Psicomotrices A Través De Programa Físico Para El Desarrollo Psicomotor En Un Niño Autista (2014)
This degree work was as thelinchpin investigate sychomotor changes through a physical program for psychomotor development in anautistic child, as it was proposed to identify, describe and then establish statistically significant changes in psychomotor development of the subject studied, evaluations in threestages, before, were performed during and after the application of the physical program. There search case study is called, the focus of there sear chis quantitative, in order to analyzethe data produced by the battery of psychomotor Victor Da Fonseca.